Morphometry of purkinje cell body of cerebellum in Bangladeshi cadaver - Haque, MA; Khalil, M; Khalil, M; Sultana, SZ; Mannan, S; Rahman, M; Ara, A; Begum, T; Choudhury, S; Haque, N (Mymensingh Medical Journal, 2010)
Mymensingh Med J. 2010 Oct;19(4):504-9 The abstract of this article is available on the PubMed website